Water mites of the genus Monatractides Viets (Acari: Hydrachnidia, Torrenticolidae) from New Guinea, with descriptions of nine new species - Pešić, Vladimir; Smit, Harry (Zootaxa, 2011)
New records of water mites of the genus Monatractides Viets, 1926 (Acari: Hydrachnidia, Torrenticolidae) from streams in Papua Province, New Guinea, Indonesia are presented. Nine new species are described: Monatractides novaeguineae, M. papuensis, M. nipsanicus, M. sentanicus, M. abepurus, M. bionus, M. sahuli, M. alticolus and M. humilis. A redescription of Monatractides papillatus (Smit, 1996) is given. A key to the species of Monatractides from Papua Province is presented.